225Ac‐PSMA‐617‐targeted alpha therapy for the treatment of metastatic castration‐resistant prostate cancer: A systematic review and meta‐analysis. Issue 9 (27th April 2021) - Ballal, Sanjana; Yadav, Madhav P.; Sahoo, Ranjit K.; Tripathi, Madhavi; Dwivedi, Sada N.; Bal, Chandrasekhar
Abstract: Background: The aim of this systematic review and meta‐analysis was to present an overview of the role of 225 Ac‐PSMA (prostate‐specific membrane antigen)‐targeted alpha therapy (TAT) as a salvage treatment option in metastatic castration‐resistant prostate cancer. Methods: A systematic literature review was performed in databases such as Medline, Embase, PubMed, Cochrane Central Register of Controlled Clinical Trials, and the website; www.ClinicalTrials.gov until December 2020. The study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guidelines. All original articles, including retrospective, prospective, hand‐searched articles, and clinical trials, were searched, and appropriate data were included for the analysis. The study's primary endpoint assessed therapeutic efficacy by biochemical response assessment criteria (any prostate‐specific antigen [PSA] decline and >50% PSA decline from the baseline) after 225 Ac‐PSMA‐TAT. The secondary endpoints included assessing overall survival (OS), progression‐free survival (PFS), molecular response, and therapy‐related adverse events across all the studies. The values were expressed as pooled proportions and demonstrated graphically by forest plots using the random‐effects model. Results: After the data extraction and filtration process, a total of three publications, including 141 patients, were included for the final analysis. The pooled proportion of patients demonstrating any PSA decline and greater than 50% PSA decline were 83% (95% confidence interval [CI]: 77%–89%) and 59% (95% CI: 42%–76%), respectively. The pooled proportions for OS was 81% (95% CI: 74%–89%). The pooled proportion of patients who have shown complete molecular response are 17% (95% CI: 5%–29%). The median PFS was 12 months (interquartile range: 8.2–14.4 months). Across the studies, the most common side effects from 225 Ac‐PSMA‐617 TAT were xerostomia/dry mouth, which pertained to Gr I–II in 63.1% (89 of 141), followed by fatigue in 44.5% (45 of 101) of patients. Grade I–II and III anemia was noted in 48.5% (49 of 101) and 6% (6 of 101), respectively. Grade III leukopenia and thrombocytopenia were negligible: 0.9% (1 of 101) and 0.9% (1 of 101), respectively. Similarly, grade III nephrotoxicity was also observed only in 5 of 101 (5%) patients. Conclusion: Treatment with 225 Ac‐PSMA‐617 TAT demonstrated biochemical response, improved survival, caused low treatment‐related toxicity proving a promising salvage treatment option in mCRPC patients.